Gender Roles in English Textbooks for Indonesian Senior High School Students: An Analysis of Bahasa Inggris and Pathway to English - Yelsa Astuti A.R; Delvi Wahyuni (Universitas Negeri Padang, 2023)
The aim of this qualitative research is to compare the gender role representation in two English textbooks for twelfth grade senior high school students. The first textbook published by Indonesian Ministry of Education and Culture and second textbook published by Erlangga. Content analysis was used as the research method of this study. Logsdon’s theory of gender representation was utilized to analyze the roles of gender representation in both textbooks. The results show that gender roles in both textbooks are dominated by male. It showed that male roles in both textbook tend to be professional occupation such as president, programmer, director, etc. in addition, female roles tend to be social occupation such us secretary, teacher, housewife, etc. in conclusion, it was also found that gender stereotype was exist in male and female occupation in both textbooks. However, when both textbooks were compared, there is more gender equality of textbook published by Indonesian Ministry of Education and Culture Bahasa Inggris than textbook published by Erlangga Pathway to English. It shows that the authors of Bahasa Inggris made an effort to promote gender equity.